Clinical study of 39 Chinese patients with arrhythmogenic right ventricular dysplasia/cardiomyopathy - Ma, Ke-juan; Li, Ning; Wang, Hong-tao; Chu, Jian-min; Fang, Pi-hua; Yao, Yan; Ma, Jian; Hua, Wei; Zhang, Shu; Wang, Fang-zheng; Li, Zhang; Pu, Jie-lin (Chinese medical journal, 2009)
Background There are few studies on the clinical profile of Chinese patients with arrhythmogenic right ventricular dysplasia/cardiomyopathy （ARVD/C）. The purpose of this study was to describe the clinical characteristics of ARVD/C patients from China, particularly to define the features of electrocardiograph and treatment outcomes. Methods Thirty-nine patients hospitalized in Fu Wai Cardiovascular Hospital from 1998 to 2006 were included. The data were obtained from the medical archive and the follow-up records. Results Of these patients 33 were male and 6 female （age at the first presentation was （34.9 ± 9.8） years）. The most common symptoms were palpitation （62%） and syncope （44%）. Right precordial QRSd 〉 110 ms was detected in 69% of the patients, epsilon wave in 59%, and a ratio of QRSd in V1＋V2＋V3/V4＋V5＋V6 ≥ 1.2 in 82%. The most frequent features of electrocardiogram in patients without right bundle-branch block were T-wave inversions and S-wave upstroke in V1-V3 〉55 ms （96% and 90% of 28 patients, respectively）. Radiofrequency catheter ablation （RFCA） for ventricular tachycardia （VT） was successful in 15 （68%） of 22 patients. The recurrence rate of VT was 46% （7/15） during the follow-up of （16.7 ± 11.2） months. Seven patients had cardioverter/defibrillator （ICD） implanted plus drug therapy and 17 patients took antiarrhythmic drugs alone. During the follow-up of （35.6 ± 19.0） months, all patients with ICD implanted received at least one appropriate ICD shock. One patient died of ventricular fibrillation suddenly and one patient underwent heart transplantation for progressive biventricular heart failure during the drug therapy alone. Conclusions This study demonstrated the clinical and ECG features of the 39 ARVD/C Chinese patients. ICD provided life-saving protection by effectively terminating malignant arrhythmias, and the high recurrence of VT was the major problem of RFCA therapy.